THE ROLE OF MUTUAL TRUST BETWEEN EMPLOYEES AND MANAGEMENT IN ENHANCING EMPLOYEE ENGAGEMENT A STUDY OF OPINIONS OF A SAMPLE OF EMPLOYEE IN MIDDLE EUPHRATES BANKS GOVERNORATES - Prof. Dr. Ihssan Dahash Chalab, Abbas Hussein Abbar Al-Karawi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research aims to uncover role of mutual trust between employees and management represented by (integrity, benevolence and ability) in enhancing employees engagement represented by (physical, cognitive engagement, and emotional engagement ). current study relied on a questionnaire tool in order to measure level of availability of mutual trust between employees and management and employee engagement with private banks in central Euphrates governorates. (Diwaniyah, al-Najaf al-Ashraf, Babil, Muthanna, and Holy Karbala) / Republic of Iraq. And by using special statistical packages in program (SPSS.V.25) and (AMOS.V.25), results of normal distribution, modeling of structural equation, reliability coefficient, internal validity, arithmetic mean, standard deviations, relative importance, and a matrix were extracted. Correlation, and regression coefficient, as results of study showed existence of a correlation and influence between mutual trust between employees and management in increasing level of employee engagement in their employee.